NLRP3 inflammasome: The rising star in cardiovascular diseases - Zheng, Yidan; Xu, Li; Dong, Nianguo; Li, Fei (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases (CVDs) are the prevalent cause of mortality around the world. Activation of inflammasome contributes to the pathological progression of cardiovascular diseases, including atherosclerosis, cardiomyopathy, abdominal aortic aneurysm, calcific aortic valve disease, heart failure, and cardio-cerebrovascular ischemic injury. The nucleotide oligomerization domain-, leucine-rich repeat-, and pyrin domain-containing protein 3 (NLRP3) inflammasome plays a critical role in the innate immune response, requiring priming and activation signals to provoke the inflammation. Evidence shows that NLRP3 inflammasome not only boosts the cleavage and release of IL-1 family cytokines, but also leads to a distinct cell programmed death: pyroptosis. The significance of NLRP3 inflammasome in the CVDs-related inflammation has been extensively explored. In this review, we summarized current understandings of the function of NLRP3 inflammasome in CVDs and discussed possible therapeutic options targeting the NLRP3 inflammasome.